Localisation of quantitative trait loci for quality attributes in a doubled haploid population of wheat (Triticum aestivum L.) - Raman, R.; Allen, H.; Diffey, Simon; Raman, H.; Martin, P.; McKelvie, K. (N R C Research Press, 2009)
Selection of wheat germplasm for a range of quality traits has been a challenging exercise because of the cost of testing, the variation within testing data, and a poor understanding of the underlying genetics. The objective of this study was to identify quantitative trait loci (QTLs) underlying quality traits in wheat. A doubled haploid population comprising 190 lines from Chara/WW2449 was grown in two different environments and evaluated for various quality traits. A molecular map comprising 362 markers based upon simple sequence repeat, sequence tagged microsatellite, glutenin, and DArT loci was constructed and subsequently exploited to identify QTLs using a whole-genome approach. Fifteen QTLs that were consistent in the two different environments were identified for thousand kernel mass, grain protein content, milling yield, flour protein content, flour colour, flour water absorption, dough development time, dough strength (extensograph height and resistance at 5 cm), and dough extensibility (extensograph length) using the whole genome average interval mapping approach. The amount of genetic variation explained by individual QTLs ranged from 3% to 49%. A number of QTLs associated with dough strength, dough extensibility, dough development time, and flour water absorption were located close to the glutenin Glu-B1 locus on chromosome 1B. Identification of the chromosomal location and effect of the QTLs influencing wheat quality may hasten the development of superior wheats for target markets via marker-assisted selection.